Uric acid : A new antioxidant in patients with pemphigus vulgaris - Maryam Yousefi; Hoda Rahimi; Behrooz Barikbin; Parviz Toossi; Sara Lotfi; Mehdi Hedayati; Shima Younespour (Wolters Kluwer Medknow Publications, 2011)
Background: Increased reactive oxygen species (ROS) and lipid peroxidation are seen in many dermatologic disorders, for example, atopic dermatitis, psoriasis, vitiligo, acne vulgaris, pemphigus vulgaris (PV), lichen planus, and alopecia areata. ROS has an important role in the inflammation process. In PV, increased production of ROS leads to decline of antioxidants in plasma and red blood cells which results in oxidative stress. We aimed to evaluate the level of these antioxidants in PV patients and compare it to the controls. Materials and Methods: Among patients attending the dermatology clinics, 30 patients with PV, who had never been on treatment, were enrolled to the study. The control group consisted of 30 age- and sex-matched healthy non-smoker individuals. Venous blood was collected from the subjects for the evaluation of plasma levels of glutathione peroxidase, vitamin C, selenium, bilirubin, and uric acid. Results: Age mean and standard deviation of the patients (40.83, 12.74) was comparable to the controls (41.96, 13.08). Mean level of uric acid was significantly lower in PV patients compared to the controls (P = 0.006). Other antioxidants were not different between the two groups. Uric acid of the patients with mucosal involvement was significantly lower than patients with mucocutaneous involvement (P = 0.049). Limitations: The blood level of other antioxidants (e.g. malondialdehyde) was not evaluated. Conclusions: Uric acid as an antioxidant in our study had similar changes to previous studies in the field of other diseases but selenium, bilirubin, and glutathione peroxidase did not differ between patients and controls.